Health Status and Access to Care among Maine’s Low-Income Childless Adults: Implications for State Medicaid Expansion - Croll, Zach; Ziller, Erika (Maine Policy Review, 2019)
The Affordable Care Act allows states to expand Medicaid coverage to low-income childless adults with income at or below 138 percent of the federal poverty level. Following a 2017 statewide referendum, Maine began enrolling eligible residents in expanded Medicaid in January 2019. While prior research suggests that Maine’s low-income childless adults may face health problems and barriers to accessing services, their health status has not been well documented. The rollout and ongoing implementation of Maine’s Medicaid expansion may be hampered by incomplete information on the characteristics and health status of the low-income childless adult population. This study examines demographic characteristics, health status, and access to care among Maine’s low-income childless adults and offers recommendations to policymakers, providers, and other stakeholders working to implement Medicaid expansion and address the health needs of this vulnerable population.